2020
DOI: 10.1177/1069072720925048
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Short Version of the Working Alliance Inventory and Its Longitudinal Measurement Invariance Across Individual Career Counseling Sessions

Abstract: The aim of the present study was 2-fold: (a) to examine the factor structure of the short version of the Working Alliance Inventory (WAI-S) in clients who were engaged in individual career counseling sessions and (b) to investigate whether the factor structure of the WAI-S is invariant across the first and the third career counseling sessions. A total of 283 clients seeking individual career counseling completed the WAI-S at the end of the first session (T1). Of the 283 clients, 217 also completed the WAI-S at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…These factors, however, were very highly correlated (0.708–0.964) as shown previously [ 101 , 104 , 105 ], raising questions about their interpretation, and limiting their use as simultaneous predictors in regression models because of multicollinearity concerns. Literature on the factor structure of the WAI(-S) in contexts other than coaching has yielded similarly inconsistent results, suggesting either a one- [ 104 , 106 ], two- [ 63 , 107 ], or three-factor structure [ 63 , 108 ]. Indeed, a more recent study [ 109 ] has suggested co-existence of general and specific working alliance factors but advised caution in the interpretation of the specific factors because they lacked uniqueness.…”
Section: Discussionmentioning
confidence: 99%
“…These factors, however, were very highly correlated (0.708–0.964) as shown previously [ 101 , 104 , 105 ], raising questions about their interpretation, and limiting their use as simultaneous predictors in regression models because of multicollinearity concerns. Literature on the factor structure of the WAI(-S) in contexts other than coaching has yielded similarly inconsistent results, suggesting either a one- [ 104 , 106 ], two- [ 63 , 107 ], or three-factor structure [ 63 , 108 ]. Indeed, a more recent study [ 109 ] has suggested co-existence of general and specific working alliance factors but advised caution in the interpretation of the specific factors because they lacked uniqueness.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument used in this study, the working alliance inventory (WAI; Horvath & Greenberg, 1989) is the most often used measure to investigate the relations between the alliance and treatment outcomes (Flückiger, Del Re, et al, 2018). The BP factor structure of the alliance over the course of treatment has been of continued interest to researchers and there is an ongoing debate whether WAI operationalizes a stable one, two, or three-factorial construct over the various stages of therapy (e.g., Andrusyna et al, 2001; Cirasola et al, 2020; Constantino et al, 2020; Corbière et al, 2006; Hukkelberg & Ogden, 2016; Kivlighan et al, 2016; Milot-Lapointe et al, 2020). The research using BP designs to investigate the factor structure of the WAI yielded inconsistent results.…”
Section: Longitudinal Investigations Of the Alliancementioning
confidence: 99%
“…Two studies, both with doubtful methodological quality, analyzed longitudinal measurement invariance of the WAI-S-P (Milot-Lapointe et al, 2020;Cirasola et al, 2021). Both studies found no significant differences across treatment sessions.…”
Section: Cross-cultural Validity/measurement Invariancementioning
confidence: 99%